Measures of Investor and Consumer Confidence and Policy Actions in the Current Crisis - Dailami, Mansoor; Masson, Paul (2012)
The current financial crisis has highlighted the danger that declines in confidence can have a self-fulfilling effect on economic activity. In this paper, the authors consider ways of measuring investor and consumer confidence, and try to explain the evolution of confidence using measures of financial volatility, investment performance, macroeconomic outcomes, and policy actions. They identify a link between investor and consumer confidence. Finally, they show that liquidity provision and easing of interest rates had only a limited effect on financial market spreads during the crisis, arguing for additional measures to address the loss of confidence. The paper focuses on the need for financial regulatory reform, and shows how the incentives to cooperate in this area are stimulated by a common shock to confidence.